In Memoriam Viorel Cosma (1923-2017): Outstanding Personality for Romanian Musicology - ȘUTEU, Cristina (Studia Universitatis Babes-Bolyai Musica, 2023)
This year marks a century since the birth of the musicologist and enescologist Viorel Cosma (1923-2017). The purpose of this article is to recall the impact that Viorel Cosma had in musicological research on a national and international level through the thousands of signed articles and through the approximately 100 books published on themes that highlighted Romanian music and musicians. The significant contributions of Viorel Cosma are recognized in particular for 22 volumes dedicated to George Enescu, for 12 biobibliographical lexicons with personalities of Romanian music, for musical criticism signed throughout 40 years at concerts as well 60 years at opera performances. Viorel Cosma remains in the history of Romanian musical culture as an emblematic personality who successfully combined the role of musicologist, teacher, enescologist, lexicographer and music critic.